Thy Kingdom Come 爾國臨格 : A Photographic History of Anglicanism in Hong Kong, Macau, and Mainland China 港澳及內地聖公宗圖片史 - Chen, Ruiwen; Wickeri, Philip L. (Philip Lauri), 1947- (Sheng Kung Hui (Series), 2019)
Celebrating the twentieth anniversary of the formation of the Hong Kong Sheng Kung Hui (Anglican Church) Province in 2018, Thy Kingdom Come: A Photographic History of Anglicanism in Hong Kong, Macau, and Mainland China is a richly illustrated history of the past 200 years. Although connected to the British colonial government, Hong Kong bishops always sought to relate the Church to Chinese society, making this story predominantly Chinese. The book is divided into five parts. Part I explores the beginnings of Anglican and Episcopal missions in China. Part II relates the history of the Chung Hua Sheng Kung Hui (CHSKH) from 1912 to 1951, a turbulent time in China, when the church's challenge was to respond to change in every facet of society. Part III illustrates the history of the Diocese from 1951 to 1981, during which new churches, schools, and clinics were established. Part IV records Hong Kong's transition from colonial rule to the return to China; it was during these years that Bishop Peter Kong-kit Kwong developed parish ministries, strengthened missions in education and social welfare, and solidified relations with the church in China. Part V describes new developments in the Hong Kong Sheng Kung Hui. With almost 200 photos, Thy Kingdom Come brings Church history to life in a way no prose history ever could.